Water-Based Supplementation Technology for Grazing Cattle in the Tropics: A Large-Scale Commercial Case Study - Eliéder Prates Romanzini; Vivienne McCollum; Sarah Mcilveen; Evandro Maia Ferreira; William Luiz de Souza; Marcelo Augusto Oliveira Castro; Priscila Arrigucci Bernardes; Ryan J. Batley; Mark G. Trotter; Diogo Fleury Azevedo Costa (Applied Sciences)
Water-based nutrient injection technology, widely used in sectors like viticulture, hydroponics, and intensive animal systems, has previously seen limited application in livestock production. Early mechanical dispensers for nutrients, such as non-protein nitrogen (NPN) and phosphorus (P), were prone to malfunction, leading to inconsistent dosing and potential livestock health risks. This contributed to skepticism and slow adoption among producers. However, recent technological advancements have renewed interest in water-based supplementation for grazing animals. This case study assessed the use of water injection technology to deliver nutrients and a methane-reducing compound to cattle on a commercial cattle station under extensive grazing conditions. A total of 120 steers [initial liveweight (LW) 322.5 ± 28.3 kg] were assigned to three groups: water only (Control), a water supplement containing nutrients such as nitrogen and phosphorus, known as uPRO GREEN® (Green), and uPRO GREEN® combined with Agolin Ruminant L® (Blue). The experiment lasted 90 days, during which LW was continuously monitored via a walk-over weighing system, and water disappearance was measured at the mob level. Methane emissions were forecasted using dry matter intake estimates based on observed animal growth rates. Additionally, 24 steers were equipped with on-animal sensors with GPS to monitor behavioral changes. The results indicate that despite the potential reduction in water intake (Control and Green: 948.1 and 973.5 L/d, respectively, versus 547.5 L/d for Blue), there were no negative effects on growth (mean average daily gain of 1.32 kg/d) or animal behaviors. The predicted methane emission of 209.04 g CH4/head/day could potentially be reduced by 10–15% with the compound used in the current trial. These findings suggest that water-based supplementation can be used to optimize nutrient delivery and a methane-reducing compound without compromising cattle productivity in extensive grazing environments. In addition, the potential enteric methane mitigation presents an opportunity for livestock producers to generate additional revenue through carbon credits or to create new markets for beef with low greenhouse gas emissions when cattle consume methane-reducing compounds.